Evaluation of design quality: a perceptive and cognitive approach - Reis, Antônio Tarcísio da Luz (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper deals with evaluation of quality of urban and building design through the perceptive and cognitive approach, adopted in the area of Environment-Behaviour Studies. The concepts of perception and cognition are defined and related to design evaluation. The importance of such approach for the qualification of the built environment is emphasized. Successful and unsuccessful urban and building designs are exemplified as consequences, respectively, of the consideration and disregard of design and evaluation of design quality approach characterized by the users’ perception of such designs or similar designs. A set of categories that define urban quality are proposed, helping to structure the physical aspects associated to the quality of the built environment. These proposed categories are based on the nature of such physical aspects concerning aesthetics, use, and the structure of the built environment.